Topological polarisation states - Saito, Shinichi (Frontiers in Physics, 2023)
Polarisation states are described by spin expectation values, known as Stokes parameters, whose trajectories in a rotationally symmetric system form a sphere named after Poincar é.Here, we show that the trajectories of broken rotational symmetric systems can exhibit distinct topological structures in polarisation states. We use a phase-shifter to form a polarisation circle (S 1 ), which interferes with the original input due to the phase change of the output state upon the rotation. By rotating the circle using a rotator, the trajectories become a polarisation torus (S 1 × S 1 ), which was experimentally confirmed in a simple set-up using passive optical components together with Mach-Zehnder interferometers. We also discuss about realisations of other topological features, such as a M öbius strip, a trefoil knot, Hopf-links, and topological Dirac bosons with a bulk-edge correspondence.